Migrant Worker Networks and Roles in Community Development through Resource Transfers - Roengsumran, Kamonwan (Journal of Community Development Research (Humanities and Social Sciences); Vol 16 No 3 (2023): July - September 2023DO - 10.14456/jcdr-hs.2023.28, 2023)
The purpose of this paper is to examine the roles of migrant worker networks in community development through the transfer of resources in the context of Samut Sakhon province. Despite disagreement over whether resource transfers across the country facilitate or thwart development (see Bartram et al., 2014), this study claims that transactions of money and knowledge, practices, and values—particularly in the destination country— can lead to community development, and that migrant networks can be counted among development actors that engage in the process of transferring resources. This study focuses on the process of resource transfers in the destination country. To understand the roles of migrant worker networks in transferring resources in Samut Sakhon province, online surveys were conducted with 94 participants, in-depth interviews conducted with 6 Mon migrant workers, and semi-structured interviews were conducted with 5 community leaders or individuals working for Mon groups. This study’s findings demonstrate that Mon migrant worker networks are engaged in the process of transferring resources through donations to network members and to Mon self-help group projects promoting Buddhism and providing for basic needs (i.e., education, food security during the COVID-19 pandemic, etc.) and through the provision of education. Furthermore, close ties (family and friends) and organizational ties (Mon self-help groups) are engaged in sharing information, knowledge, perceptions, and experiences within networks. Joining and collaborating with Mon self-help groups and participation in community activities are kinds of an engagement in the process of resource transfers seen in this context. Trust is a significant factor that encourages migrant workers to transfer resources within their networks. Actions of engaging in the process of resource transfers built on trust benefit the community and bring about community development in the destination country, since those actions’ outcomes represent a high level of agency and strengthened solidarity, as following Bhattacharyya’s (1995) community development perspective. Donation for religious-related projects, joining and working for Mon self-help groups and participating in community events/activities lead to strengthened solidarity due to shared interests being strengthened, while donation for promoting education, the provision of education and sharing the perceptions, experiences, knowledge, etc. within the migrant worker networks lead to a high level of agency because of migrant workers’ increasing capability indicated by their better job opportunity and income. However, when creating conditions conducive to community development, a balance between solidarity and agency is necessary. Keywords: Migrant Worker Network, Migrant Workers, Resource Transfer, Community Development